PENGARUH GREEN ACCOUNTING DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN SEKTOR BASIC MATERIAL DI BEI - Mirna Wati; Arnadi Chairunnas; Sasmita Nabila Syahrir (Jurnal Akuntansi Kompetif, 2026)
The objective of this study is to analyze the impact of green accounting and firm size on the performance of companies in the raw materials sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. A quantitative approach using associative methods was applied in this study. Secondary data refers to data that is utilized and obtained from sustainability reports, annual reports, and the PROPER rankings issued by the KLHK. Purposive sampling was the technique used, resulting in a sample of 14 companies and a total of 56 observations. The steps of data analysis using multiple linear regression via software, after passing classical assumption tests including multicollinearity, normality, heterocedasticity, and autocorrelation tests. The results obtained are green accounting has a positive and significant effect on company performance, indicating that better implementation of environmental accounting improves company performance. Firm size also has a positive and significant effect on company performance, suggesting that larger companies have better capabilities in generating optimal performance. Simultaneously, green accounting and firm size have a significant effect on company performance, indicating that both variables jointly contribute to improving company performance. This study implies that companies in the raw materials sector need to make efforts to improve the implementation of green accounting and optimize their resource management practices in order to enhance their sustainability performance. This study can also be used as a source of information for regulators and investors in considering environmental aspects and firm size in decision-making